Preparation method of high-purity aluminum wire for vacuum coating, high-purity aluminum wire and application of high-purity aluminum wire
By controlling the content and surface quality of metal impurities in high-purity aluminum wire, the problem of splashing during vacuum evaporation is solved, and the high-performance preparation of composite liquid-collection aluminum film is achieved.
Patent Information
- Application Number
- CN202510104407.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-23
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-01-23
AI Technical Summary
During vacuum evaporation, the splashing phenomenon occurs due to the high impurity content of aluminum wire, large intermetallic compound size, and poor surface quality during vacuum evaporation, which affects the surface quality and performance of the composite liquid collector aluminum film.
By controlling the content of metal impurities in high-purity aluminum wire, reducing the number and size of the second phase, degassing the aluminum liquid, controlling the oxide film thickness and grain size of the aluminum wire surface, and improving the strength and surface quality of the aluminum wire by drawing and scraping.
The splashing phenomenon of aluminum wire during the evaporation process is reduced, and the composite aluminum film obtained has excellent performance, with a square resistance in the TD direction of ≤29mΩ/sq, a surface roughness Sa≤0.18μm, a tensile strength≥215MPa, a pinhole ratio≤0.02ea/m2, and a good adhesion.
Smart Images

Figure CN119870198A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of high-purity aluminum preparation, and in particular to a method for preparing a high-purity aluminum wire for vacuum coating, the high-purity aluminum wire and applications thereof. Background Art
[0002] In recent years, new energy vehicles have developed rapidly, and the safety requirements for batteries have become increasingly higher. The composite material for the positive current collector of new energy batteries adopts a sandwich structure, consisting of a polymer material in the middle and a metal stacking layer on both sides, and is generally produced by vacuum coating. The vacuum-evaporated composite current collector aluminum film has significant advantages, higher safety performance, and will fuse when overheated to prevent explosions. It also has a good weight reduction effect. The composite current collector aluminum film can reduce weight by 48.1% compared to traditional aluminum film. However, due to factors such as splashing during the evaporation process, pinholes are easily formed, affecting the surface quality of the composite current collector aluminum film, limiting its scope of application.
[0003] During vacuum evaporation, the aluminum wire changes from solid to liquid on the evaporation boat, and then diffuses from liquid to gas. The evaporation goes through three states: solid, liquid, and gas. When the fine solid is given energy by the hot gas, splashing occurs. In addition to the material, state, and evaporation process of the evaporation boat, the purity of the aluminum wire, the size and quantity of the compound, the surface quality, and the thickness of the oxide film will also have a direct impact on the splashing, thereby affecting the splashing and causing too many pinholes in the aluminum film. Summary of the invention
[0004] In view of the problem in the above-mentioned prior art that splashing occurs during the evaporation process of aluminum wire due to high impurity content, large size of intermetallic compounds, poor surface quality, etc., which affects the surface quality and performance of the composite current collector aluminum film, the present invention provides a method for preparing high-purity aluminum wire for vacuum coating, high-purity aluminum wire and application thereof.
[0005] To achieve the above object, the technical solution of the present invention is as follows:
[0006] A method for preparing high-purity aluminum wire for vacuum coating comprises the following steps:
[0007] (1) adding an aluminum ingot into a smelting furnace to melt into aluminum liquid, transferring the aluminum liquid into a holding furnace for degassing, the pressure in the furnace being 0.3-1.0 MPa, introducing Ar gas into the aluminum liquid to obtain an aluminum liquid with a hydrogen content of ≤0.10 mL / 100 g;
[0008] (2) using a casting machine to continuously cast the aluminum liquid obtained in step (1) at a casting temperature of 700-730° C. to obtain a cast billet, removing an oxide film on the surface of the cast billet by scraping, and rolling the cast billet at a starting rolling temperature of 400-450° C. and a final rolling temperature of 280-320° C. to obtain a high-purity aluminum wire rod;
[0009] (3) The high-purity aluminum wire rod obtained in step (2) is subjected to 6-10 rough drawing, 1-3 fine drawing and 2-3 wire scraping treatments to obtain high-purity aluminum wire for vacuum coating.
[0010] Furthermore, in step (1), the continuous casting adopts automatic control of water pressure by zones.
[0011] Furthermore, the diameter of the high-purity aluminum wire rod described in step (2) is 8-10 mm.
[0012] Furthermore, in step (2), the rolling speed is 2-5 m / s.
[0013] Furthermore, in step (3), the diameter of the aluminum wire after rough drawing is 2.6-2.8 mm, the diameter of the aluminum wire after fine drawing is 2.1-2.2 mm, and the diameter of the aluminum wire after scraping treatment is 1.8-2.0 mm.
[0014] The present invention also includes the following technical solutions:
[0015] A high-purity aluminum wire for vacuum coating, the chemical composition of which includes, by mass percentage, Al 99.92-99.98%, Fe≤0.005%, Si≤0.004%, Cu≤0.0001%, Mn≤0.0001%, Mg≤0.0002%, Cr≤0.0001%, Zn≤0.0001%, V≤0.0001%, Ti≤0.0008%, Bi≤0.0001%, and the remainder is inevitable impurities.
[0016] Furthermore, the surface roughness Sa of the aluminum wire is ≤0.2 μm, the thickness of the oxide film is ≤100 nm, the conductivity is ≥64.2% IACS, and the tensile strength is 140-160 MPa.
[0017] Furthermore, the aluminum wire contains an intermetallic compound AlFeSi phase, and the AlFeSi phase is in a granular form with a size of ≤2 μm.
[0018] The present invention also includes the following technical solutions:
[0019] A composite current collector aluminum film produced by vacuum evaporation of high-purity aluminum wire for vacuum coating.
[0020] Furthermore, the sheet resistance of the composite aluminum film in the TD direction is ≤29mΩ / sq, the surface roughness Sa is ≤0.18μm, the tensile strength is ≥215MPa, and the pinhole rate is ≤0.02ea / m 2 , the adhesion is achieved by using 3M tape to stick to the aluminum film surface without the aluminum foil falling off.
[0021] The mechanism involved in the present invention is as follows:
[0022] Due to the high melting point of the impurity elements in the aluminum wire, the second phase formed by the impurity elements during the vacuum evaporation process is not easy to melt, and it is easy to produce splashing, which affects the performance of the vacuum evaporated composite current collector aluminum film. When the Fe content in the aluminum wire does not exceed 0.005%, it mainly forms a granular AlFeSi phase with a smaller size, which is not easy to produce splashing during the vacuum coating process; but when the Fe content exceeds 0.005%, it is easy to form a large-sized flocculent or blocky Fe phase, which is easy to produce splashing, so its content needs to be controlled below 0.005%. Si and Fe elements can form AlFeSi phases together, but the Si content affects the number and size of AlFeSi phases. When the Si content exceeds 0.004%, AlFeSi phases with a large number and large size are prone to splashing during the evaporation process. The content of Cu, Mg, Mn, Cr, Zn, and Ti elements needs to be controlled below 100ppm to avoid splashing.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] The present invention reduces the amount and size of the second phase by controlling the content of metal impurities in the high-purity aluminum wire, performs degassing treatment on the aluminum liquid so that the hydrogen content in the aluminum liquid is ≤0.10mL / 100g, and the impurity content in the high-purity aluminum wire is relatively low; the thickness of the oxide film and the grain size on the surface of the aluminum wire are controlled by controlling the starting and final rolling temperatures, and no intermediate annealing treatment is performed to avoid the thickening of the oxide film on the surface of the aluminum wire; the strength and surface quality of the aluminum wire are improved by drawing and scraping treatment; the improvement of the above performance reduces the splashing phenomenon of the aluminum wire during the evaporation process, and the composite aluminum film obtained by vacuum evaporation has excellent performance, and its square resistance in the TD direction is ≤29mΩ / sq, the surface roughness Sa is ≤0.18μm, the tensile strength is ≥215MPa, and the pinhole rate is ≤0.02ea / m 2 , the adhesion is achieved by using 3M tape to stick to the aluminum film surface without the aluminum foil falling off. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] The embodiments of the present invention are further described below with reference to the accompanying drawings, in which:
[0026] Figure 1 The second phase of the aluminum wire for vacuum coating in Example 1 is shown;
[0027] Figure 2 The surface roughness of the aluminum wire for vacuum coating in Example 1 is shown;
[0028] Figure 3 The thickness of the oxide film of the aluminum wire for vacuum deposition in Example 1 is shown. DETAILED DESCRIPTION
[0029] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below through specific embodiments in conjunction with the accompanying drawings. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0030] Example 1
[0031] A method for preparing high-purity aluminum wire for vacuum coating comprises the following steps:
[0032] (1) adding an aluminum ingot into a smelting furnace to melt into aluminum liquid, transferring the aluminum liquid into a holding furnace for degassing, the pressure in the furnace being 0.3 MPa, introducing Ar gas into the aluminum liquid to obtain an aluminum liquid with a hydrogen content of 0.10 mL / 100 g;
[0033] (2) using a casting machine to continuously cast the aluminum liquid obtained in step (1) at 700° C. to obtain a cast billet, removing the oxide film on the surface of the cast billet by scraping, and rolling the cast billet at a starting rolling temperature of 400° C., a rolling speed of 3.5 m / s, and a final rolling temperature of 300° C. to obtain a high-purity aluminum wire rod with a rod diameter of 9.5 mm;
[0034] (3) The high-purity aluminum wire rod obtained in step (2) is subjected to 7 rough drawing to a diameter of 2.7 mm, 2 fine drawing to a diameter of 2.12 mm, and 2 wire scraping treatments to a diameter of 2.0 mm to obtain a high-purity aluminum wire for vacuum coating.
[0035] In this embodiment, the high-purity aluminum wire for vacuum coating has the following chemical compositions by mass percentage: Al 99.98%, Fe 0.003%, Si 0.002%, Cu 0.0001%, Mn 0.0001%, Mg 0.0002%, Cr 0.0001%, Zn 0.0001%, V 0.0001%, Ti 0.0008%, Bi 0.0001%, and the remainder is unavoidable impurities.
[0036] Example 2
[0037] A method for preparing high-purity aluminum wire for vacuum coating comprises the following steps:
[0038] (1) adding an aluminum ingot into a smelting furnace to melt into aluminum liquid, transferring the aluminum liquid into a holding furnace for degassing, the pressure in the furnace being 1.0 MPa, introducing Ar gas into the aluminum liquid to obtain an aluminum liquid with a hydrogen content of 0.09 mL / 100 g;
[0039] (2) using a casting machine to continuously cast the aluminum liquid obtained in step (1) at 730° C. to obtain a cast billet, removing the oxide film on the surface of the cast billet by scraping, and rolling the cast billet at a starting rolling temperature of 380° C., a rolling speed of 3.2 m / s, and a final rolling temperature of 310° C. to obtain a high-purity aluminum wire rod with a rod diameter of 10.0 mm;
[0040] (3) The high-purity aluminum wire rod obtained in step (2) is subjected to 8 rough drawing processes to a diameter of 2.8 mm, 3 fine drawing processes to a diameter of 1.95 mm, and 2 wire scraping processes to a diameter of 1.8 mm to obtain a high-purity aluminum wire for vacuum coating.
[0041] In this embodiment, the high-purity aluminum wire used for vacuum coating has a chemical composition, by mass percentage, of Al 99.92%, Fe 0.005%, Si 0.004%, Cu 0.0001%, Mn 0.0001%, Mg 0.0002%, Cr 0.0001%, Zn 0.0001%, V 0.0001%, Ti 0.0008%, Bi 0.0001%, and the remainder is unavoidable impurities.
[0042] Example 3
[0043] The difference from Example 1 is that the starting rolling temperature is 420°C and the finishing rolling temperature is 310°C.
[0044] Example 4
[0045] The difference from Example 1 is that the high-purity aluminum wire rod is roughly drawn 7 times to a diameter of 2.6 mm.
[0046] Example 5
[0047] The difference from Example 1 is that the high-purity aluminum wire rod is precision-drawn to a diameter of 2.2 mm.
[0048] Example 6
[0049] The difference from Example 1 is that the high-purity aluminum wire rod is subjected to wire scraping treatment three times until the diameter is 1.9 mm.
[0050] Comparative Example 1
[0051] The difference from Example 1 is that the high-purity aluminum wire for vacuum coating comprises, by mass percentage, the following chemical components: Al 99.75%, Fe 0.06%, Si 0.05%, Cu 0.0015%, Mn 0.002%, Mg 0.0002%, Cr 0.001%, Zn 0.001%, V 0.001%, Ti 0.01%, Bi 0.001%, and the remainder is unavoidable impurities.
[0052] Comparative Example 2
[0053] A method for preparing high-purity aluminum wire for vacuum coating comprises the following steps:
[0054] (1) adding an aluminum ingot into a smelting furnace to melt into aluminum liquid, transferring the aluminum liquid into a holding furnace for degassing, the pressure in the furnace being 0.1 MPa, introducing Ar gas into the aluminum liquid, and obtaining an aluminum liquid with a hydrogen content of 0.17 mL / 100 g;
[0055] (2) using a casting machine to continuously cast the aluminum liquid obtained in step (1) at 730° C. to obtain a cast billet, and rolling the cast billet at a starting rolling temperature of 500° C., a rolling speed of 2.2 m / s, and a final rolling temperature of 350° C. to obtain a high-purity aluminum wire rod with a rod diameter of 10.0 mm;
[0056] (3) The high-purity aluminum wire rod obtained in step (2) is subjected to four rough drawing to a diameter of 5.2 mm, annealed at 450° C. for 2 h, then finely drawn three times to a diameter of 2.2 mm and scraped twice to a diameter of 2.0 mm, to obtain high-purity aluminum wire for vacuum coating.
[0057] In this comparative example, the chemical composition of the high-purity aluminum wire for vacuum coating is the same as that in Example 2.
[0058] The properties of the high-purity aluminum wires for vacuum coating prepared in various embodiments and comparative examples are shown in Table 1.
[0059] Table 1
[0060]
[0061] The high-purity aluminum wires prepared in the above embodiment and comparative example were vacuum coated respectively, and the vacuum degree of the coating was higher than 10 -3 Pa, a 6μm PET was selected as the substrate, and a 1μm composite current collector aluminum film was plated on the upper and lower surfaces of the PET. The performance of the obtained composite aluminum film in the TD direction was tested. The results are shown in Table 2. The adhesion was achieved by sticking the aluminum film surface with 3M tape. No aluminum foil falling off indicated that the adhesion met the requirements.
[0062] Table 2
[0063]
[0064] The present invention reduces the amount and size of the second phase by controlling the content of metal impurities in the high-purity aluminum wire, performs degassing treatment on the aluminum liquid so that the hydrogen content in the aluminum liquid is ≤0.10mL / 100g, and the impurity content in the high-purity aluminum wire is relatively low; the thickness of the oxide film and the grain size on the surface of the aluminum wire are controlled by controlling the starting and final rolling temperatures, and no intermediate annealing treatment is performed to avoid the thickening of the oxide film on the surface of the aluminum wire; the strength and surface quality of the aluminum wire are improved by drawing and scraping treatment; the improvement of the above performance reduces the splashing phenomenon of the aluminum wire during the evaporation process, and the composite aluminum film obtained by vacuum evaporation has excellent performance, and its square resistance in the TD direction is ≤29mΩ / sq, the surface roughness Sa is ≤0.18μm, the tensile strength is ≥215MPa, and the pinhole rate is ≤0.02ea / m 2 , the adhesion is achieved by using 3M tape to stick to the aluminum film surface without the aluminum foil falling off.
[0065] Some exemplary embodiments of the present invention are described above. It can be understood that the above embodiments are only used to explain the present invention and do not constitute a limitation on the protection scope of the present invention. The features in these embodiments can be recombined in a suitable manner, and the scheme obtained thereby is still within the protection scope required by the present invention. Based on the above embodiments, all other embodiments obtained by those skilled in the art without making creative work, that is, all modifications, equivalent substitutions and improvements made within the spirit and principles of this application, fall within the protection scope required by the present invention.
Claims
1. A method for preparing high-purity aluminum wire for vacuum coating, characterized in that: The following steps are involved: (1) adding an aluminum ingot into a smelting furnace to melt into aluminum liquid, transferring the aluminum liquid into a holding furnace for degassing, the pressure in the furnace being 0.3-1.0 MPa, introducing Ar gas into the aluminum liquid to obtain an aluminum liquid with a hydrogen content of ≤0.10 mL / 100 g; (2) using a casting machine to continuously cast the aluminum liquid obtained in step (1) at a casting temperature of 700-730° C. to obtain a cast billet, removing an oxide film on the surface of the cast billet by scraping, and rolling the cast billet at a starting rolling temperature of 400-450° C. and a final rolling temperature of 280-320° C. to obtain a high-purity aluminum wire rod; (3) The high-purity aluminum wire rod obtained in step (2) is subjected to 6-10 rough drawing, 1-3 fine drawing and 2-3 wire scraping treatments to obtain high-purity aluminum wire for vacuum coating.
2. The method for preparing a high-purity aluminum wire for vacuum coating according to claim 1, characterized in that: In step (1), the continuous casting adopts automatic water pressure control in different zones.
3. The method for preparing a high-purity aluminum wire for vacuum coating according to claim 1, characterized in that: The diameter of the high-purity aluminum wire rod described in step (2) is 8-10 mm.
4. The method for preparing a high-purity aluminum wire for vacuum coating according to claim 1, characterized in that: The rolling speed in step (2) is 2-5 m / s.
5. The method for preparing a high-purity aluminum wire for vacuum coating according to claim 1, characterized in that: In step (3), the diameter of the aluminum wire after rough drawing is 2.6-2.8 mm, the diameter of the aluminum wire after fine drawing is 2.1-2.2 mm, and the diameter of the aluminum wire after scraping treatment is 1.8-2.0 mm.
6. A high-purity aluminum wire for vacuum coating prepared by the method according to any one of claims 1 to 5, characterized in that: Its chemical composition includes by mass percentage: Al 99.92-99.98%, Fe≤0.005%, Si≤0.004%, Cu≤0.0001%, Mn≤0.0001%, Mg≤0.0002%, Cr≤0.0001%, Zn≤0.0001%, V≤0.0001%, Ti≤0.0008%, Bi≤0.0001%, and the balance is inevitable impurities.
7. The high-purity aluminum wire for vacuum coating according to claim 1, characterized in that: The surface roughness of the aluminum wire is Sa≤0.2μm, the oxide film thickness is ≤100nm, the conductivity is ≥64.2%IACS, and the tensile strength is 140-160MPa.
8. The high-purity aluminum wire for vacuum coating according to claim 1 or 2, characterized in that: The aluminum wire contains an intermetallic compound AlFeSi phase, which is in a granular form with a size of ≤2 μm.
9. A composite current collector aluminum film vacuum-deposited using the high-purity aluminum wire for vacuum coating as claimed in any one of claims 6 to 7.
10. The composite current collector aluminum film according to claim 9, characterized in that: The square resistance of the composite aluminum film in the TD direction is ≤29mΩ / sq, the surface roughness Sa is ≤0.18μm, the tensile strength is ≥215MPa, and the pinhole rate is ≤0.02ea / m 2 , the adhesion is achieved by using 3M tape to stick to the aluminum film surface without the aluminum foil falling off.
Citation Information
Patent Citations
Soft aluminum wire and preparation method thereof
CN110643843A
Preparation method of high-conductivity pure aluminum wire
CN115945618A
Aluminum wire, composite aluminum film, detection method, preparation method and battery
CN117702054A
High-conductivity heat-resistant high-elongation aluminum alloy wire and application thereof
CN118957364A
Metal structure, method for manufacturing the same, method for manufacturing vapor deposition film using metal structure
JP2024123365A